Using a Logic Model to Direct Backward Design of Curriculum - Aria Mia Loberti (American Society for Microbiology, 2018)
Contemporary approaches to STEM course design typically encourage the backward design of curricula. This is to say that the learning activities and assessments of the course are explicitly guided by the learning outcomes of the course. Less discussed is the fact that this paradigm is also used in nonacademic settings. From this perspective, drawing from the nonacademic world, we discuss the use of a logic model approach as a structured, orderly way to implement backward design. We use the design and implementation of an introductory biology class to illustrate how a logic model template helped frame our inclusive, Freirean approach to teaching and learning.